DETERMINANT OF WORK DISCIPLINE, WORK EMPOWERMENT AND WORK MOTIVATION FOR EMPLOYEE PERFORMANCE AT THE BATAM OFFICE AND SPECIAL PORT AUTHORITY - Agus Ardiansa; Eko Prasetyo; Sumardin Sumardin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The purpose of this study was to determine the performance of employees in the secretariat of the Regional Representative Council Office of Batam City. Respondents in this study were 40 respondents, all of whom were State Civil Servants (ASN) at the Batam City Regional Representative Council Office. The data collection method in this research is by using a questionnaire. The type of research used is quantitative research. The variables of this study consist of three independent variables, namely Work Discipline, Work Empowerment and Work Motivation and Employee Performance as the dependent variable. The results of this study are the Anova test produces an F count of 136,121> F table 2.87 with a significance level (probability number) of 0.05. F count> F table then Ho is rejected and H1 is accepted. Then the regression coefficient of Work Discipline, Work Empowerment and Work Motivation together has a significant effect on Employee Performance variables